DESIGN OF THE SI-NANING MOBILE APP AS A DIGITAL INTERVENTION FOR ANEMIA AND STUNTING PREVENTION - Fidyah Aminin; Rahmadona, Rahmadona (International Journal of Social Science, 2025)
Stunting is a problem that needs special attention because of its high prevalence in Indonesia. Anemia in pregnant women is one of the factors that causes stunting. Based on preliminary studies, in Tanjungpinang City, there has been no digitization of Health Education about the prevention of anemia and stunting. This research aims to design and build an Android application called "Si-NaNing as an information medium for anemia and stunting prevention. The research methods used include information content planning, data and software needs used as well as application system development using the Rapid Application Development (RAD) method. The results of the development of the Si-Naning application will provide convenience in providing health education related to anemia and stunting, and can be used to improve the knowledge, attitude, motivation, and independence of pregnant women in the prevention of anemia and stunting.